PENGEMBANGAN MEDIA KOMIK TEMATIK ISLAMI - Nurul Fadillah; Nirwana Anas; Rora Rizky Wandini (Universitas Negeri Medan, 2021)
This study aims to develop Islamic Thematic Comics as a valid, practical and effective learning media. The methods used in this study were validation sheets, questionnaires and learning outcomes tests. The type of this research is R&R research with Borg and Gall research design. The results showed that the Islamic Thematic Comic product based on the value given by the valid validator obtained a value of 94.01% in the